ANALISA PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. BANK MANDIRI (PERSERO) TBK MAKASSAR) - Adrianus Parenden (Jurnal Bisnis dan Kewirausahaan, 2015)
The Effect of Job Motivation Analysis of Employee Performance (Case Studi at PT. Bank Mandiri (Persero) Tbk Makassar), This study aimed to clarify whether the variable Job Motivation significant influence on employee performance at PT. Bank Mandiri (Persero) Tbk. Makassar. The sample of using purposive sampling method is directly choosing 50 persons of the employees. The data collection methods that used were interview the parties that involved with the issues being discussed directly and gave questionnaires to the employees in accordance with the research conducted. The data were analyzed with using Qualitative and Quantitative Methods that using five formulas; Simple Regression Analysis, Correlation Analysis, Test T-test, F test and the coefficient of determination (R2) test with the aid of SPSS 18.0 software for windows. The results showed that jointly Job Motivation significantly influence the performance of employees at PT. Bank Mandiri (Persero) Tbk Makassar. Variable Job Motivation regression coefficients positive (+) indicates a unidirectional relationship, in other words, Job Motivation will improve the performance of employees at PT. Bank Mandiri (Persero) Tbk Makassar. The correlation or the relationship between Job Motivation Employee Performance Performance Work with PT. Bank Mandiri (Persero) Makassar is very strong for (r = 0.923) and the coefficient of determination or the number of Rsquare is 0.853.